The roles of exosomal circular RNAs in cancer. Issue 9 (31st July 2020) - Gao, Nan; Shi, Fangzhou; Song, Dandan; Xuan, Wei
Abstract: Despite the development of therapeutic strategies, cancer is the second death cause worldwide and still rising. Unclear molecular mechanisms of carcinogenesis and lack of biomarkers for early diagnosis or advanced management are responsible for the poor prognosis of cancer. Recently, exosomes have been the focus of tumor studies, as they carry many biomolecules including proteins, lipids, and nucleic acids, and transfer them to participate in tumor development. Among the biomolecules, noncoding RNAs including microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs) in exosomes have been found to participate in carcinogenesis and gain more attention. Compared with lncRNAs and miRNAs, the exosomal circRNAs are less studied in tumor studies. However, circRNAs are enriched and more stable in exosomes because of their covalently closed‐loop structures, protection provided by exosomes, and protein binding partners. Furthermore, exosomal circRNAs display more potent sponge effect for miRNAs, as they contain more miRNA response elements than lncRNAs. In this review, we highlighted the functional roles of exosomal circRNAs on the tumor progression including tumor growth, invasion, metabolism, immunomodulation, and chemotherapeutic drug resistance. Moreover, we also summarized predictive potency and clinical use of exosomal circRNAs in cancer.